The Influence Of Leadership Style On Employee Performance: A Case Study At PT Sako Indah Gemilang, Palembang City - Marlina Marlina; Esty Naruliza; R.Y Effendi; Hermantoalyafiq Hermantoalyafiq (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to determine the influence of leadership style on employee performance at PT. Sako Indah Gemilang Palembang. The results of the analysis show that leadership style has a positive and significant effect on employee performance, with a calculated t value of 8.088 greater than the t table of 0.1832, and a significance value of 0.000 which is smaller than 0.05. This finding proves that the alternative hypothesis stating that there is an influence of leadership style on employee performance is acceptable. Effective leadership can create a conducive work atmosphere, increase motivation, and encourage productivity. Conversely, authoritarian leadership or less open communication has the potential to reduce work enthusiasm and trigger conflict. Therefore, companies need to implement a fair, open, and supportive leadership style so that employees feel appreciated, motivated, and able to provide optimal performance.